Genetic diversity of the declining arable plant Centaurea cyanus: population fragmentation within an agricultural landscape is not associated with enhanced spatial genetic structure. (9th May 2014) - Le Corre, V; Bellanger, S; Guillemin, J‐P; Darmency, H; Lutman, Peter
Summary Agricultural intensification has recently resulted in the decrease in frequency and abundance of arable weed species. This includes the previously widespread Centaurea cyanus, whose populations are now fragmented and infrequent in western Europe. The consequences of habitat modification and fragmentation in terms of genetic diversity of the remaining populations have not yet been addressed. We used ten microsatellite markers to assess the genetic diversity and genetic structure of populations contained in an agricultural landscape in north‐eastern France. The ten microsatellites were all highly polymorphic. Centaurea cyanus appears to be a genetically variable species, with high levels of genetic diversity within each cultivated field. Genetic structure was investigated using a Bayesian method. The partitioning of the genetic variation into three clusters was not associated with sampling locations, and most individuals were admixed. These results suggest that the cornflower populations investigated may have multiple origins in the past and that genetic variation has been reshuffled by human transportation of seeds. Thus, anthropogenic dispersal associated with farming activities is probably a major factor driving the structure of genetic diversity in arable land plants. Despite low levels of genetic differentiation between populations, fine‐scale spatial genetic structure was observed within populations, suggesting limited local dispersal. We conclude that in areas where C. cyanus has become rare, the recent fragmentation of populations may in the future cause a loss of genetic diversity and even extinction.